2020
DOI: 10.3319/tao.2019.11.27.01
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization effect on the observed changes of surface air temperature in Northeast China

Abstract: Although many studies have analyzed the effects of urbanization on temperature changes, the urbanization's effect on temperature change remains controversial. Northeast China is the largest old industrial base in China, which experienced a rapid urbanization in the past decades. Under the background of climate change, understanding the changes of surface air temperature and urbanization effects on temperature changes in the Northeast China is important to predict climate change in China. By analyzing the histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…The pattern of urbanization contribution to DayHot is different from that to CoHot, particularly in western and parts of southeastern Europe, and western United States, where the urbanization shows slightly cooling effect on DayHot (Figures 3d–3f). Recent studies have found that local hydroclimate plays an important role in the urbanization effects (Liao et al., 2018; Lin et al., 2020), and the regional disparity in the hydroclimate conditions, such as shading, aerosols, and thermal inertia differences between urban and rural areas, could lead to different urbanization effects on daytime and nighttime temperature (Kalnay & Cai, 2003; Shen et al., 2020). However, the mechanism of urbanization effects on CoHot events is more complex and needs further study.…”
Section: Resultsmentioning
confidence: 99%
“…The pattern of urbanization contribution to DayHot is different from that to CoHot, particularly in western and parts of southeastern Europe, and western United States, where the urbanization shows slightly cooling effect on DayHot (Figures 3d–3f). Recent studies have found that local hydroclimate plays an important role in the urbanization effects (Liao et al., 2018; Lin et al., 2020), and the regional disparity in the hydroclimate conditions, such as shading, aerosols, and thermal inertia differences between urban and rural areas, could lead to different urbanization effects on daytime and nighttime temperature (Kalnay & Cai, 2003; Shen et al., 2020). However, the mechanism of urbanization effects on CoHot events is more complex and needs further study.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Shen et al . (2020) have found that in Northeast China, a significant urbanization effect was observed in T min during night‐time, whereas, a different effect was observed on T max during day time under the different changes of solar radiation; and (b) the vertical temperature profiles in the lower atmosphere (Jacobson, 1999; Fujibe, 2012). During night‐time, the formation of UHI is influenced by a strong surface inversion that originates in the sub‐urban region but is destroyed over the urban surface (Oke and East, 1971).…”
Section: Resultsmentioning
confidence: 99%
“…Though various factors are proved to be related with global warming (Dong et al, 2014;Zhang et al, 2016;Zhang et al, 2017;Wei et al, 2018;Qiu et al, 2020;Shen et al, 2020), surface solar radiation is indubitable the most direct influencing factor for variations of Tmax, and CO 2 contributes significantly to variations of Tmin. Research shows that a CO 2 concentration increasing of 22 ppm can increase 10% of the longwave radiation, which is very important for variations of Tmin (Feldman et al, 2015).…”
Section: Possible Driving Mechanism Of the Asymmetric Warming At Diff...mentioning
confidence: 99%